Efficient and transgene-free genome editing in wheat through transient expression of CRISPR/Cas9 DNA or RNA - Yi Zhang; Zhen Liang; Yuan Zong; Yanpeng Wang; Jinxing Liu; Kunling Chen; Jin-Long Qiu; Caixia Gao (Nature Communications)
Abstract Editing plant genomes is technically challenging in hard-to-transform plants and usually involves transgenic intermediates, which causes regulatory concerns. Here we report two simple and efficient genome-editing methods in which plants are regenerated from callus cells transiently expressing CRISPR/Cas9 introduced as DNA or RNA. This transient expression-based genome-editing system is highly efficient and specific for producing transgene-free and homozygous wheat mutants in the T0 generation. We demonstrate our protocol to edit genes in hexaploid bread wheat and tetraploid durum wheat, and show that we are able to generate mutants with no detectable transgenes. Our methods may be applicable to other plant species, thus offering the potential to accelerate basic and applied plant genome-engineering research.